Prevention of chronic kidney disease progression in patients with acute decompensation of chronic heart failure - V. V. Davydov; E. L. Arekhina (Российский кардиологический журнал)
Aim. To assess the efficiency of the program of prevention of chronic kidney disease (CKD) progression in patients with acute decompensation of chronic heart failure (CHF). The program included the use of nitrendipine, a calcium channel antagonist, and the replacement of single intravenous bolus dosing of furosemide with a prolonged intravenous infusion in the early stage of the disease.Material and methods. One hundred twenty five patients with decompensation of CHF were examined and divided into 2 groups. Group 1 received standard therapy. In the group 2, an additional prevention program was carried out. The criterion of CKD progression was the change in glomerular filtration rate (GFR) in accordance with the KDIGO guidelines (2012). GFR was calculated by two methods: serum creatinine and cystatin C levels. The parameters were monitored and compared with baseline levels at admission to the hospital and on the 10th day of therapy. For the initial level was taken the patient’s GFR, calculated by the serum creatinine level prior to the present hospitalization on the background of a satisfactory condition.Results. At admission to the hospital, in group 1 CKD progression was established in 33,3% of patients, in group 2 — in 29,3%. On the 10th day, CKD progression was noted in 47,4% of patients in group 1, in group 2 — in 23,4%.Conclusion. The prevention program allows to reduce the number of cases of CKD progression in patients with decompensation of CHF by 2 times.